2019
DOI: 10.1108/ijsms-08-2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

Blinded by the sand of its burrowing? Examining fans’ intentions to follow one-day cricket on TV with a moderating effect of social influence

Abstract: Purpose The purpose of this paper is to investigate the effect of patriotism, nostalgia, drama and excitement of the game, and interest in star players to predict fans’ intentions to follow one-day cricket in near future. Furthermore, social influence is positioned as a moderator to enrich the understanding of fans’ motives to follow one-day cricket. Design/methodology/approach The data are collected by means of a cross-sectional survey conducted among 609 university students enroled in Pakistani and Sri Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 111 publications
(193 reference statements)
1
27
0
Order By: Relevance
“…According to Meng et al (2015), it is difficult to single out one factor that may lead to a fans' identification with a particular team. As a whole, it could be a mix of several intangible factors, such as their opinions and feelings towards a variety of elements and experiences (Kashif et al , 2019; Kim and Gower, 2017; Lock and Heere, 2017; Prayag et al , 2019; Toder-Alon et al , 2019; Trail et al , 2017). Sports fans' identification with a particular team because of the attachment points has several implications for both the fans and the team in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Meng et al (2015), it is difficult to single out one factor that may lead to a fans' identification with a particular team. As a whole, it could be a mix of several intangible factors, such as their opinions and feelings towards a variety of elements and experiences (Kashif et al , 2019; Kim and Gower, 2017; Lock and Heere, 2017; Prayag et al , 2019; Toder-Alon et al , 2019; Trail et al , 2017). Sports fans' identification with a particular team because of the attachment points has several implications for both the fans and the team in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [47], it was found that groups have a significant effect on consumer motivation regarding certain products. Social comparison theory argues that consumer emotions and cognition set grounds by which people compare themselves with others over certain kinds of consumer products [58,59]. Studies on culture and consumer anticonsumption are limited and should be pursued to reveal new insights into anticonsumption behavior [46].…”
Section: Sociocultural Factors and Soft Drink Anticonsumption Behaviormentioning
confidence: 99%
“…Similarly, drama and excitement were found to be another important intentional factor for watching cricket tournaments (Eddosary et al, 2015). Subsequently, Kashif et al (2019) reported that nostalgic associations are one of the reasons why people watch sporting events, particularly cricket tournaments, in groups; however, individuals' nostalgic associations with cricket as a sport are widely overlooked (Cho et al, 2014). Furthermore, Stevens and Rosenberger (2012) highlighted that previous studies conducted in this domain have examined star players as a source of identity formation; hence, this factor plays the role of an intentional antecedent for watching cricket or any other sport.…”
Section: Introductionmentioning
confidence: 94%
“…While exploring fans' intentions and their antecedents for watching sporting events, we identified patriotism (developing group solidarity and social identity) as one of the prime intentional motives for watching a sporting event (Kashif et al, 2019). Similarly, drama and excitement were found to be another important intentional factor for watching cricket tournaments (Eddosary et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation